The Influence of Guidance and Counseling on Students' Social-Emotional Development: Pengaruh Bimbingan dan Konseling terhadap Perkembangan Sosial Emosional Peserta Didik - Muda, Indra; Hartati, Diah Vitaloka; Nurmala, Eka; Siregar, Muhammad Sapril; R., Sulastriani (PT. Alpha Trianguli Australis, 2025)
Students' social and emotional development is an important aspect in the world of education that contributes to academic success and psychological well-being. Guidance and counseling in schools is not only limited to individual interventions but also includes group counseling, social skills development programs, and support for students who experience emotional and social problems. The method used in this study is the Systematic Literature Review (SLR), which involves searching, selecting, analyzing, and synthesizing relevant literature. The results of this study are: 1) Guidance and counseling significantly impact students' social and emotional development. This service not only helps in improving social skills but also plays a role in managing emotions and reducing stress; and 2) To improve the effectiveness of BK, it is necessary to increase the number of counselors, training for educators, and socialization to students and parents regarding the importance of BK services.